A study of soil characteristics of road damages in Jeram, Kuala Selangor - Intan Najiha Akhmar, Saharuddin; Doh, Shu Ing (IOP Publishing, 2021)
The main purpose of this research work is to identify the classification and strength of soil does it affected the road damages in Jeram, Kuala Selangor. The most factors influencing road damages in Jeram is an overloading vehicle using the main roads. To achieve the objectives of this paper soil laboratory testing has been done in justify the content of peat soil. Location of study can be categorizing as a plantation soil as there are a majority of land has been use in agricultural sector which are oil palm tree plantation. Besides, oil palm plantation suitable for peat soil land which has less soil strength. Sample of soil were collected in Jeram and bring it to soil mechanics and geotechnical laboratory in UMP. Few tests were being soil classification, particle size distribution, moisture content, density, specific gravity, Atterberg limit and direct shear test. Soil sample from three different roads were chosen which are Jalan Pantai Jeram, Jalan Simpang 3 Jeram and Jalan Tambak Tengah. The road has different criteria from the surface damages which no damages occur, less damage and most damages on road. From the data collected, Jalan Simpang 3 Jeram results the most damages road and the less strength of soil due to high content of peat soil. The soils criteria are located near trench and in the area of oil palm plantation. It also is the main road were used to collect the plantation yield to the factory.